Best practices in poverty reduction : an analytical framework - Oyen, Else; International Studies in Poverty Research (London Zed Books, 2002)
Poverty reduction has come to be proclaimed as the core function of international development agencies, including the World Bank. This book focuses on a notion of best practice, and the key role which it can potentially play in strengthening anti-poverty strategies. Contributors explore the social and organizational factors influencing the transition of an ordinary particular anti-poverty project or strategy into becoming established as best practice. They examine the critical policy-relevant aspect of the conditions under which a best practice, once identified, and embedded as it is in a social setting, can be successfully transferred to other situations and countries.
Keywords: Pobreza -- Países en desarrollo